The Natural Harmony of Interests: Adam Smith and the Political Philosophy of the Classical School - Marie Correa; Brandon K. Dumas; Chanika Jones; Victor Mbarika (Centre for Behaviour and Wellness Advocacy, 2017)
This paper explores the idea of laissez-faire and economic liberation as a corollary to the emergence of the national economy. It discusses the extent to which the individual actor as identified in Adam Smith's economic philosophy is fundamental to the societal economy. It also reviews the essential role played by the individual actor towards the shaping of national or public policy. Some authors suggest that economic freedom increases economic growth, however for economies that are emerging, it is better for the state to control, regulate and invest in economic activities until their industries are strong enough to engage in competition with large firms from developed nations.